A numerical study on the effect of gasoline-hydrogen fuel blend on engine power and torque - Noor Hizam Dzulkharnain, Mohd Hassan (2010)
This report was about the effect of gasoline-hydrogen fuel blend on engine power and torque. The experiment had been done by using different ratios of gasoline and hydrogen fuel. In this simulation, the ratio of gasoline and hydrogen were varied in order to analyze the power and torque of the engine. The engine modelling was drawn by GT-Power software and was analyzed by GT-Post software. The ratios that had been used in this analysis were by increment of 10% for hydrogen fuel and decrement of 10% for gasoline fuel until both fuel reached 50%. The engine that has been used was a single cylinder engine with four stroke cycle, by using SI-inject. The values for the power and torque of the engine is increased by the increasing of fuel ratio at both engine speeds. The values of engine power were increasing even though we run it at 3000 rpm and 6000 rpm but as for the torque, the values were higher at 3000 rpm but decreasing at 6000 rpm.